PENGELOLAAN ASET DESA BANJAR PANJANG KECAMATAN KERUMUTAN KABUPATEN PELALAWAN TAHUN 2022 - Rahma, Suci Salsa Aulia; Hadi, Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Villages have assets that can be utilized to increase income for the village, which falls under the village's original income, such as Banjar Panjang Village, which has a vast village treasury land asset that should prosper its community and building assets used for village governance and facilitating the public interest of the village community. Desa Banjar Panjang has utilized the village treasury land assets through a rental system since ancient times, but it was not optimal due to the rental payment system. In 2022, the village government improved the rental payment system, resulting in increased income from the rental of the village treasury land assets. However, there was an issue because the government's focus on improvements was only on assets with economic value. Good asset management must optimize village assets, both economically valuable assets and building and infrastructure assets, as well as other goods. The purpose of this research is to analyze the asset management of Banjar Panjang Village, Kerumutan District, Pelalawan Regency in 2022. The research approach used is a qualitative approach with a descriptive research type. The location of this research is in Banjar Panjang Village. The types and sources of data in this research are divided into primary data and secondary data. Data collection techniques through interviews and documentation. Data analysis techniques through data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the management of village assets in its implementation is not yet optimal due to the lack of understanding among village officials regarding the management of village assets. In the planning of village assets outlined in the Village Medium-Term Development Plan (RPJM Desa) for the procurement and planning of village assets, community participation is not involved. The utilization of village assets through the village land lease system and village-owned housing lease has not been optimal. Securing village assets through legal and physical protection. The administration of village assets is not yet optimal due to the lack of village officials who are experts in asset inventorying. Keywords: Village asset management, planning, utilization, security, and administration.